Diagnostic and Therapeutic Use of Botox for Breast Reconstruction - Ma, Irene T; Yesantharao, Pooja; Darrach, Halley M; Seither, Jennifer G; He, Hui; Nguyen, Dung H (Archives of Clinical and Medical Case Reports, 2021)
Introduction: Breast reconstruction is most commonly performed using implant-based reconstruction. Patients with subpectoral implant placement with or without latissimus dorsi (LD) muscle coverage can experience muscle pain and animation deformity. Due to minimal literature describing the use of botulinum toxin (BTX-A) treatment for these side effects from implant-based reconstruction, we report our outcomes. Methods: A retrospective chart review of breast reconstructive patients for a single surgeon was performed. Patients who underwent BTX-A injection for muscular pain, spasm, or animation deformity were identified and outcomes reviewed. They were also stratified based on radiation treatment and type of muscle flap used. Results: Eleven patients were identified who had a submuscular pectoralis pocket and/or a pedicled latissimus dorsi flap. Nineteen breasts were treated. The average amount of time from the patient’s last surgery to BTX-A injection was 11.2 months. 25-100 units were used per injection with an average of 60 units. Non-irradiated patients had signifycantly lower post-injection capsular contracture Baker grades and significantly lower amounts of BTX-A were injected. Patients who had both pectoralis major muscle and LD implant-reconstruction were significantly less likely to have improvement in pain/tightness. Most patients reported improvement or resolution of their pain and/or animation deformities. Conclusion: Implant-based reconstruction using the pectoralis major and/or LD muscles can be plagued with muscular pain, spasm, and animation deformities. The use of BTX-A is a diagnostic and therapeutic modality for these postbreast reconstruction patients with most patients having resolution of symptoms without the need for additional surgery